Pemanfaatan Abu Hasil Gasifikasi Sekam Padi Menjadi Silika Gel - Ani Purwanti (Institut Teknologi Nasional Yogyakarta, 2024)
The rice milling industry produces 35% rice husk, which contains silica (SiO2) as one of its main components. Rice husk comprises water (9.02%), ash (17.71%), and carbohydrates (33.71%). Silica gel is derived from the coagulation of sodium silicate (NaSiO₂) sol and is highly porous, making it effective in moisture adsorption. Utilizing rice husk for silica gel production presents an efficient solution. Rice husk gasification transforms biomass waste into syngas, with ash as a byproduct. This study involved processing rice husk ash from gasification into sodium silicate, followed by a sol-gel process using both strong and weak acids to produce silica gel. Gasification was performed at 750 °C for 5 hours. The ash was ground and sieved (150 mesh). Extraction was conducted at 80°C for 1 hour using 1N NaOH, after which acid was added until the pH reached 7. The acids used were 1N HCl and acetic acid . The mixture was heated to 80°C until the silica gel reached a constant weight. The resulting silica gel was analyzed using FT-IR and tested for air moisture adsorption. The synthesis of silica gel using HCl yielded less product compared to using CH3COOH. FT-IR analysis of the rice husk ash silica gel indicated the presence of Si-OH and Si-O-Si functional groups. In the water adsorption test, silica gel synthesized with strong acid (HCl) exhibited higher water adsorption capability compared to silica gel synthesized with weak acid (CH3COOH).